They ask you answer : a revolutionary approach to inbound sales, content marketing, and today's digital consumer - Sheridan, Marcus (Wiley, 2017)
"This book will not just tell the incredibly practical and extraordinarily simple story of River Pools and Spas, but it will also dissect how other companies of various industries have managed to find exceptional results applying these same principles, making it relatable to all industries, businesses, and entrepreneurs alike"--